Cell Death and Ageing – A Question of Cell Type - Pidder Jansen-Dürr (The Scientific World Journal)
Replicative senescence of human cells in primary culture is a widely accepted model for studying the molecular mechanisms of human ageing. The standard model used for studying human ageing consists of fibroblasts explanted from the skin and grown into in vitro senescence. From this model, we have learned much about molecular mechanisms underlying the human ageing process; however, the model presents clear limitations. In particular, a long-standing dogma holds that replicative senescence involves resistance to apoptosis, a belief that has led to considerable confusion concerning the role of apoptosis during human ageing. While there are data suggesting that apoptotic cell death plays a key role for ageing in vitro and in the pathogenesis of various age-associated diseases, this is not reflected in the current literature on in vitro senescence. In this article, I summarize key findings concerning the relationship between apoptosis and ageing in vivo and also review the literature concerning the role of apoptosis during in vitro senescence. Recent experimental findings, summarized in this article, suggest that apoptotic cell death (and probably other forms of cell death) are important features of the ageing process that can also be recapitulated in tissue culture systems to some extent. Another important lesson to learn from these studies is that mechanisms of in vivo senescence differ considerably between various histotypes.